Gut Microbiome of Coexisting BaAka Pygmies and Bantu Reflects Gradients of Traditional Subsistence Patterns - Gomez, Andres; Petrzelkova, Klara J; Burns, Michael B; Yeoman, Carl J; Amato, Katherine R; Vlckova, Klara; Modry, David; Todd, Angelique; Jost Robinson, Carolyn A; Remis, Melissa J; Torralba, Manolito G; Morton, Elise; et al. (Cell reports, 2016)
To understand how the gut microbiome is impacted by human adaptation to varying environments, we explored gut bacterial communities in the BaAka rainforest hunter-gatherers and their agriculturalist Bantu neighbors in the Central African Republic. Although the microbiome of both groups is compositionally similar, hunter-gatherers harbor increased abundance of Prevotellaceae, Treponema, and Clostridiaceae, while the Bantu gut microbiome is dominated by Firmicutes. Comparisons with US Americans reveal microbiome differences between Africans and westerners but show western-like features in the Bantu, including an increased abundance of predictive carbohydrate and xenobiotic metabolic pathways. In contrast, the hunter-gatherer gut shows increased abundance of predicted virulence, amino acid, and vitamin metabolism functions, as well as dominance of lipid and amino-acid-derived metabolites, as determined through metabolomics. Our results demonstrate gradients of traditional subsistence patterns in two neighboring African groups and highlight the adaptability of the microbiome in response to host ecology.
Keywords: Diet, Paleolithic; bakteriální RNA; střevní mikroflóra; RNA, Ribosomal, 16S; Humans; molekulární typizace; západní dieta; Gastrointestinal Microbiome; RNA ribozomální 16S; černoši; sekvenční analýza RNA; Spojené státy americké; Firmicutes; genové regulační sítě; mužské pohlaví; Středoafrická republika; paleolitická dieta; Molecular Typing; Sequence Analysis, RNA; Genes, Bacterial; ženské pohlaví; Gene Regulatory Networks; United States; Central African Republic; lidé; bakteriální geny; Bacteroidetes; RNA, Bacterial; Black People; Male; Diet, Western; Female